The Requirements for Long-Run Fiscal Sustainability - Robert A Buckle; Amy A Cruickshank (New Zealand Government, The Treasury, 2013)
New Zealand, like many other countries, is experiencing a changing demographic profile from one dominated by young people during the 20th century to one where the population is more evenly distributed across age groups. This has implications for the economy and society, including the government's fiscal position in the future and for the sustainability of its spending programmes. This paper discusses the link between the government budget constraint and fiscal sustainability, how fiscal sustainability can be measured and why it's important. We also examine the Treasury's current approach to modelling the extent of fiscal adjustment required and options available to achieve this adjustment. The paper proposes criteria to evaluate potential policy changes to address these long-term fiscal challenges and suggests areas where further work could be worthwhile.
Keywords: E61; E62; H68; 330; Long-run fiscal sustainability; fiscal consolidation; public debt; public social expenditure; taxation